Are there autochthonous Ferrissia (Mollusca: Planorbidae) in the Palaearctic? Molecular evidence of a widespread North American invasion of the Old World. Issue 1 (1st January 2017) - Vecchioni, L.; Marrone, F.; Arculeo, M.; Arizza, V.
Abstract: In the last few decades, findings of freshwater limpets belonging to the genus Ferrissia have been frequent and widely distributed throughout the Palaearctic and beyond. The widespread presence of a Nearctic alien taxon was proved, but no consensus was achieved about the possible existence of autochthonous Ferrissia taxa in the area, an occurrence which would be supported by the presence of gastropod fossils attributed to the genus throughout Eurasia and North Africa. In order to test the hypothesis of a possible persistence of autochthonous Ferrissia taxa in the Palaearctic to the present day, all the published data on the genetic diversity of Ferrissia populations occurring in the area were reviewed, expanding also the currently available dataset through dedicated sampling surveys in Italy, Malta and Spain. Here, based on currently published and novel large ribosomal subunit 16S rRNA (16S) and cytochrome oxidase sub-unit 1 (COI) sequences, the presence of the allochthonous Ferrissia californica in the whole Palaearctic was confirmed. Conversely, no evidence supporting the presence of autochthonous Ferrissia taxa was obtained. Ferrissia californica proved to be a highly invasive taxon (in spite of its extremely low genetic diversity) throughout the invaded regions, which is possibly related to the species’ ability of asexual reproduction. Finally, the need to investigate the possible impact exerted by F. californica on the autochthonous Palaearctic biota is briefly stressed.